PROCESS OF THE TRANSFORMATION OF PEACEFULNESS INTO MORAL NEED OF SPIRITUAL ASCENSION - Muhammadievich, Juraev Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
This article analyzes the importance of the idea of peace in the spiritual upheaval. It is explained that peace is a solid basis for the social, economic, political and spiritual development of the country and its rightful place in the world community.